2019
DOI: 10.33155/j.ramd.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia y etiología de las lesiones deportivas en jugadores de voleibol

Abstract: El objetivo de este trabajo fue realizar una revisión bibliográfica de la incidencia de lesiones derivadas de la práctica del voleibol y su relación con variables sociodemográficas y de entrenamiento. Se analizaron veinte artículos, en español o en inglés, derivados de la búsqueda en PubMed, ISI Web of Knowledge y SportDiscus. Se encontró que las lesiones son de carácter predominantemente agudo, destacando el esguince del ligamento peroneo-astragalino anterior; la rotura del ligamento cruzado anterior; y las l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In soccer, for example, significant differences have been found between early and late maturing players in variables such as muscle power, speed, body mass, height, body fat, flexibility, lower limb strength, and cardiorespiratory capacity (Gouvea et al, 2016). As a result, it is usually the early-maturing players who have greater opportunities to access specialized training and highperformance processes, while the late-maturing players are often excluded from these development opportunities (Albaladejo-Saura et al, 2022;Cobley, 2017). In relation to the latter, recent research found that late-maturing players accounted for less than 5% of the U15 and U17 cohorts in an English soccer academy (Johnson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In soccer, for example, significant differences have been found between early and late maturing players in variables such as muscle power, speed, body mass, height, body fat, flexibility, lower limb strength, and cardiorespiratory capacity (Gouvea et al, 2016). As a result, it is usually the early-maturing players who have greater opportunities to access specialized training and highperformance processes, while the late-maturing players are often excluded from these development opportunities (Albaladejo-Saura et al, 2022;Cobley, 2017). In relation to the latter, recent research found that late-maturing players accounted for less than 5% of the U15 and U17 cohorts in an English soccer academy (Johnson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%